Selected fairy tales Collins Classics - Andersen, Hans Chritian (London : Harper Collins Publisher, 2014)
This collection brings together some of Hans Christian Andersen$1 (Bs most beloved and timeless fairy tales, including classics like The Little Mermaid, The Ugly Duckling, The Snow Queen, and The Emperor$1 (Bs New Clothes. Blending fantasy, moral lessons, and emotional depth, Andersen$1 (Bs stories explore themes of kindness, courage, sacrifice, and the triumph of truth. The Collins Classics edition presents these tales in their original literary style, making them accessible to both young readers and adults who enjoy the charm of traditional storytelling.s
Keywords: English - Fiction Book